English for international tourism : intermediate coursebook - Strutt, Peter, ....- (Harlow : Pearson Education Limited, 2013)
The series builds learner confidence in the professional skills needed for the tourist industry whilst developing their language awareness. Students practise these skills in realistic Case Studies that reflect topical tourism issues. The DVD-ROM accompanying the Coursebook includes travel DVDs with accompanying worksheets. English for International Tourism is recommended preparation for the LCCI English for tourism exams www.lcci.org.uk.
Keywords: Engels ; toerisme; Engels Leermiddelen